2018
DOI: 10.1007/s11238-017-9652-6
|View full text |Cite
|
Sign up to set email alerts
|

Prosocial consequences of third-party anger

Abstract: Anger has traditionally been associated with aggression and antagonistic behavior. A series of studies revealed that experiences of third-party anger (anger experienced when observing that harm is done to someone) can also lead to prosocial behavior. More specifically, three studies, hypothetical scenarios as well as a behavioral study, revealed that third-party anger can promote compensation of the victim. The results also showed a preference for such prosocial behaviors over antagonistic behaviors. We conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 47 publications
1
24
0
1
Order By: Relevance
“…Discrimination can lead to negative psychological outcomes and it is common for marginalized individuals to feel anger in response to learning about societal inequality (Montada & Schneider, 1989). However, for some, that anger can be an important motivator of critical action (Thomas, Mavor, & McGarty, 2012;Van Doorn, Zeelenberg, & Breugelmans, 2014;Wray-Lake et al, 2018). Although numerous studies have linked racial discrimination with devastating outcomes (e.g., Brondolo, Gallo, & Myers, 2009), our findings call upon scholars to further consider how socialization messages from parents and schools can transmute anger or other negative emotions into critical agency without harm to overall well-being.…”
Section: Well-beingmentioning
confidence: 99%
“…Discrimination can lead to negative psychological outcomes and it is common for marginalized individuals to feel anger in response to learning about societal inequality (Montada & Schneider, 1989). However, for some, that anger can be an important motivator of critical action (Thomas, Mavor, & McGarty, 2012;Van Doorn, Zeelenberg, & Breugelmans, 2014;Wray-Lake et al, 2018). Although numerous studies have linked racial discrimination with devastating outcomes (e.g., Brondolo, Gallo, & Myers, 2009), our findings call upon scholars to further consider how socialization messages from parents and schools can transmute anger or other negative emotions into critical agency without harm to overall well-being.…”
Section: Well-beingmentioning
confidence: 99%
“…For example, in studies by Lotz et al (2011) and Van Doorn et al (2018), people observed a game played by two players (an allocator and a recipient) in which a certain amount of money needed to be divided. If allocators decided to allocate only a small amount of money to the other player, the third parties more often chose to spend their own money to compensate victims for their losses instead of punishing allocators for making the unfair distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, similar to personal anger, empathic anger is likely to direct action towards retaliation against a transgressor, but importantly also towards the promotion of the interests of the victim of the observed harm (Frijda, 1988). Consistently, several studies found that, in addition to a wish to punish transgressors, feelings of empathic anger were also strongly associated with a desire to help victims (Gummerum, Van Dillen, Van Dijk, & L opez-P erez, 2016;van Doorn, Zeelenberg, Breugelmans, Berger, & Okimoto, 2018;Vitaglione & Barnett, 2003). In line with these findings, Kish-Gephart, Detert, Treviño, and Edmondson (2009) suggested empathic anger as a possible way to overcome fear-based silence when individuals observe mistreatment of others (Kirrane, O'Shea, Buckley, Grazi, & Prout, 2017).…”
Section: Emotional Displays By Male and Female Leadersmentioning
confidence: 80%